Effects of Organic Solvents Exposure on Nervous System among Migrant Workers in a Toy Manufacturing Factory, Pathumthani Province - Atenta, Keremas; Thetkathuek, Anamai; Phatrabuddha, Nantaporn; Kunawudhi, Garnchit; Chernbumrung, Theerasit; Na Songkhla, Krida (Thai Journal of Toxicology, 2019)
The objective of this study is to study the effects on the nervous system from organic solvents exposure among 103 Cambodian workers each group consist of exposed group and control group working in a toy manufacturing factory, Pathumthani Province. Data collection by using the interview questionnaire for neurological disorder assessment which was modified from the Euroquest Questionnaire (EQ) standard questionnaire. The result of data analysis using descriptive statistics found that most exposed group workers are male, age 20-29 years, average age is 28.7 (SD = 5.5) years, graduated grade one to six and worked for 1.7 (SD = 0.8) years. The results of the neurological disorders analysis from the questionnaire revealed that migrant workers had symptoms of both acute and chronic neurotoxicity and had symptoms for 3 or more in every symptom domains. The result of data analysis using Binary logistic regression found that workers who graduated grade one to six have more chronic symptom of the Psychosomatic symptom domain with OR (95% CI) 2.373 (1.094, 5.146). Male workers have more chronic symptom of the Sleep disturbance symptom domain than female with OR (95% CI) 4.000 (1.029, 15.546). In summary, the results from this study can be disseminated to educate entrepreneurs and organic solvents exposed workers to prevent health problems. The interview questionnaire can be used as a screening tool for further diagnosis of neurological symptoms in high-risk workers.